(untitled) (Asian Journal of Pharmaceutics (AJP), 2021)
Ever since in January 2020, the WHO declared an international public health emergency, emerged as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (Coronavirus disease-19) pandemic which has devastated human race with its human-to-human transmission, mutation, and mortality with complex pathogenicity mechanism. Earlier theories postulated it to have emerged from â€œWet Market,â€ Huanan Seafood Wholesale Market in Wuhan city of Hubei Province in China. Based on initial speculations, this pandemic was suggested to be of enzootic origin, considerably bats and pangolins as connecting link between human-animal transmissions, which were later refuted. Time bound and effective Test, Track, and Treat policy initiatives taken by Indian Government proved to be a benchmark in controlling the pandemic, up to certain extent. Molecular diagnostics have witnessed a scaled up trend in terms of reverse transcription polymerase chain reaction and Rapid Antigen Tests to detect the contagion in oro-pharyngeal and naso-pharyngeal swabs. It is imperative that frequent mutations in SARS-CoV-2 lead to development of new serotypes making screening for novel therapeutics or repurposing of drugs cumbersome. With an effort to consummate existing clinico-pharamaceutical gaps to curb SARS-CoV-2, ardent remains the fact that plants have been considered as medicinal power houses. Green therapeutics are formulation of active phyto components when administered, enhance the bio-availability through different drug delivery systems. Exploration of medicinal plants for their bio-active ingredients to develop immune-boosters as an antiviral prophylactic tool against SARS-CoV-2 remains a preferred choice among health-care practitioners, pharmacologists, and life sciences fraternity at large. In addition, indigenous vaccines have been granted approval for Emergency Use Authorization which would help lower the rates of transmission and mortality by significant numbers in times to come.